Subdural empyema secondary to contralateral sinusitis: hematogenous dissemination? - Emerson Kennedy Ribeiro de Andrade Filho; José Eduardo Nóbrega Moura; Heitor Dutra de Medeiros; Francisco de Assis Fernandes Tavares; Rivus Ferreira Arruda (Brazilian Society for Pediatric Neurosurgery, 2023)
Sinusitis refers to inflammation in the sinuses. Complications of sinusitis are rare and most often affect the orbit. However, in rare cases, these complications may be intracranial. One of these intracranial complications is subdural empyema, which is a loculated suppuration between the dura mater and the arachnoid. Despite its rarity, it has a high mortality rate and is often underestimated by physicians. We report here a rare case of a 5-year-old girl with a subdural empyema secondary to contralateral sinusitis. She was admitted to a local hospital complaining of fever, nasal congestion and headache for 6 days. Antibiotic therapy was initiated on admission. After six days, the patient maintained the previous symptoms and developed a decreased level of consciousness, a right hemiparesis and had a witnessed tonic-clonic seizure. This prompt her transfer to a tertiary hospital for brain computed tomography (CT) scan, which revealed a left subdural collection and a right maxillo-sphenoid sinusitis. She was referred to neurosurgical care and underwent surgical drainage of the empyema. There were another two complications of sinusitis: periorbital cellulitis and frontal osteomyelitis (both on the right). The patient was discharged from the tertiary hospital on day 39 without neurological sequelae. This case shows a rare complication of sinusitis and its clinical, surgical and radiological features and reinforces to physicians the importance of being aware of the possible complications of sinusitis. The peculiarity of the case is attributable to the way in which bacterial spread from sinusitis to a contralateral subdural empyema occurred.